2012
DOI: 10.1093/nar/gks770
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA copy number is regulated in a tissue specific manner by DNA methylation of the nuclear-encoded DNA polymerase gamma A

Abstract: DNA methylation is an essential mechanism controlling gene expression during differentiation and development. We investigated the epigenetic regulation of the nuclear-encoded, mitochondrial DNA (mtDNA) polymerase γ catalytic subunit (PolgA) by examining the methylation status of a CpG island within exon 2 of PolgA. Bisulphite sequencing identified low methylation levels (<10%) within exon 2 of mouse oocytes, blastocysts and embryonic stem cells (ESCs), while somatic tissues contained significantly higher level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
137
3
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(144 citation statements)
references
References 72 publications
3
137
3
1
Order By: Relevance
“…These studies demonstrate the influence of the nucleus, whether through genetic or epigenetic means, on mtDNA segregation (Dunbar et al 1995) and tissue-specific regulation of mtDNA variants. As the variations in our mini-pig model were mainly restricted to highrespiratory tissues (brain, diaphragm, muscle, liver, heart, and fat), this suggests that there is epigenetic regulation of variant load to ensure the regulation of OXPHOS performance, which is reflected by higher mtDNA copy number (Kelly et al 2012;St John 2014). For example, for adipose tissue, this would link OXPHOS regulation to adipogenesis (Hofmann et al 2012), insulin metabolism (Ryu et al 2013), and thermogenesis (Duteil et al 2014).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These studies demonstrate the influence of the nucleus, whether through genetic or epigenetic means, on mtDNA segregation (Dunbar et al 1995) and tissue-specific regulation of mtDNA variants. As the variations in our mini-pig model were mainly restricted to highrespiratory tissues (brain, diaphragm, muscle, liver, heart, and fat), this suggests that there is epigenetic regulation of variant load to ensure the regulation of OXPHOS performance, which is reflected by higher mtDNA copy number (Kelly et al 2012;St John 2014). For example, for adipose tissue, this would link OXPHOS regulation to adipogenesis (Hofmann et al 2012), insulin metabolism (Ryu et al 2013), and thermogenesis (Duteil et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Cells can regulate the replication of their mtDNA copy number to maintain a specific set point for biosynthesis of OXPHOS subunits, which, together with the nuclear-encoded subunits, support the production of ATP by the electron transport chain (Kelly et al 2012). Among the mini-pig samples, high-respiratory tissues showed lower variant load correlated with increased mtDNA copy number.…”
Section: Discussionmentioning
confidence: 99%
“…The median fractional concentration of plasma mitochondrial DNA was only 0.00045% in healthy subjects. This fractional concentration is relatively low, considering that the size of mitochondrial genome is 0.00053% of the size of the nuclear genome and there are 50-4,000 mitochondria per cell (46,47). The smaller size distribution and relatively low abundance of circulating mitochondrial DNA is likely to be due to the higher susceptibility of mitochondrial DNA to degradation due to the absence of histone protection.…”
Section: Discussionmentioning
confidence: 99%
“…Postfertilization, oocyte-derived mitochondria are segregated into each embryonic daughter cell until the blastocyst stage, at which point the pluripotent ICM cells establish a threshold mtDNA set point from which they commence mtDNA replication in a differentiation-specified manner (37,78). Because oocyte-derived mitochondria give rise to the entire complement of mitochondria in offspring tissues, their transmission, replication, and inheritance are tightly regulated; however, this process is sensitive to maternal metabolic status and stress such as obesity (37,78). Similar to what we found in a genetic mouse model of female obesity (88), we found that mtDNA copy number was reduced in fetal livers of female and male offspring from maternal HFD exposure, with levels not being further reduced by the addition of paternal obesity.…”
Section: Alterations To Fetal Health From Combined Paternal and Matermentioning
confidence: 99%